2016
DOI: 10.1108/jm2-09-2013-0041
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the barriers of service adoption in rural Indian telecom using integrated ISM-ANP

Abstract: Purpose – This paper aims to understand and identify the various barriers in adopting new telecom services in rural areas for improving the penetration and revenue of the telecom companies. These barriers are modeled to study their inter-relationships and prioritize them for strategizing appropriate management action plans. Design/methodology/approach – Delphi technique has been used to form a consensus with the telecom managers working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…Organizational performance measurement system is important Lean Six Sigma enabler (LSSE) for monitoring the effectiveness on the inputs given to the system (Kumar Sharma and Bhat, 2014). Measuring the organizational performance helps in providing necessary feedback to the management and taking initiatives for corrective measures (Bhadani et al , 2016a). Customer satisfaction directly builds up a healthy future of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizational performance measurement system is important Lean Six Sigma enabler (LSSE) for monitoring the effectiveness on the inputs given to the system (Kumar Sharma and Bhat, 2014). Measuring the organizational performance helps in providing necessary feedback to the management and taking initiatives for corrective measures (Bhadani et al , 2016a). Customer satisfaction directly builds up a healthy future of the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, other studies (Wyche and Steinfield, 2015;Bhadani et al, 2016;Wyche and Baumer, 2016) have found specific challenges of IT adoption among the poor. Bhadani et al (2016) found that the number of mobile users adopting the e-services could be increased through fair and transparent charges by mobile operators, treating complaints on an urgent basis, and if incentive-based schemes could be introduced to improve mobile subscriptions.…”
Section: Trust Justice and Users Of E-welfare Benefitsmentioning
confidence: 69%
“…Similarly, other studies (Wyche and Steinfield, 2015;Bhadani et al, 2016;Wyche and Baumer, 2016) have found specific challenges of IT adoption among the poor. Bhadani et al (2016) found that the number of mobile users adopting the e-services could be increased through fair and transparent charges by mobile operators, treating complaints on an urgent basis, and if incentive-based schemes could be introduced to improve mobile subscriptions. Wyche and Steinfield (2015) examined the low mobile user adoption numbers among Kenyan smallholder farmers for the agricultural market information service, which is an application that sends farmers crop pricing information via short message service.…”
Section: Trust Justice and Users Of E-welfare Benefitsmentioning
confidence: 69%
“…[22] and [23] formulate the structure of a system consisting of 9 elements, namely (1) and (9) Institutions involved in the implementation of the program. There is a criteria element linkage in knowledge management [31], the interaction constraints in total quality management [32]; understand the elements of entrepreneurial constraints [33], the priority strategy [34], determine the critical success factors [30], also uses one element [35]. Several previous studies used the ISM with one element for the development of the institution's management business [36]; [37]; [38]; [39]; [40]; [41].…”
Section: Results and Discussion Structure On Institutional Systemmentioning
confidence: 99%